2020
DOI: 10.1002/maco.202011766
|View full text |Cite
|
Sign up to set email alerts
|

AVM nuclear glass/steel/claystone system altered by Callovo–Oxfordian poral water with and without cement–bentonite grout at 70°C

Abstract: The effect of a cement-bentonite grout material (CBG) was studied through glass/steel interactions. Hence 2 experimental mock-ups, consisting of a "sandwich" of 4 materials in contact: stainlesssteel/AVM glass/AVM glass/P285NH steel, were leached by Callovo-Oxfordian poral water at 70°C for 1 year. CBG material was added for one experiment, whereas the second one was CBG-free. Chemical and structural analyses (SEM-EDS, Raman), performed mainly at the AVM glass/P285NH interface, evidenced a comparable alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Silica consumption can then lead to glass corrosion. Indeed, the study of Carriere et al (2021) identified phyllosilicate phases on the glass-steel interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silica consumption can then lead to glass corrosion. Indeed, the study of Carriere et al (2021) identified phyllosilicate phases on the glass-steel interface.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of phyllosilicates in the Fe-Si-O-H system has been reported in various geological and engineering settings: on meteorites (Elmaleh et al, 2015;Lauretta et al, 2000;Muller et al, 1979;Zolensky et al, 1993;Zolotov, 2014), on Mars (Bishop et al, 2008;Ehlmann et al, 2011), in deep-sea sediments (Badaut et al, 1985(Badaut et al, , 1992Baldermann et al, 2015;Marcus & Lam, 2014), in iron-banded formations (Eugster & Chou, 1973;Grubb, 1971), in ore deposits (Inoué & Kogure, 2016;Rasmussen et al, 1998;Rivas-Sanchez et al, 2006), at iron-clay (Lanson et al, 2012;Le Pape et al, 2015;Pignatelli et al, 2014) and steel-glass interfaces (Carriere et al, 2017(Carriere et al, , 2021Schlegel et al, 2016), and as a scale deposit in brinehandling equipment (Manceau et al, 1995). Thermodynamic modeling for some of these settings has been performed with the intention of estimating the physicochemical conditions which led to the formation of these minerals in the past (Chevrier et al, 2007;Fritz & Toth, 1997;Zolotov, 2014), or of estimating the evolution of physicochemical conditions for a given mineralogical composition with time (Ngo et al, 2015;Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the progressive glass alteration process, the use of glass beaker and glass sample holder may induce ion-exchange mechanisms between silicon and iron ions [44][45][46]. We thus decided to perform additional post-mortem analysis on these glass elements.…”
Section: Commenté [Lg5]: Lina S Version On Comment 38mentioning
confidence: 99%